Adverse maternal outcomes associated with fetal macrosomia: what are the risk factors beyond birthweight? - Fuchs, Florent (BioMed Central, 2013)
BACKGROUND: To identify risk factors, beyond fetal weight, associated with adverse maternal outcomes in delivering infants with a birthweight of 4000 g or greater, and to quantify their role in maternal complications. METHODS: All women (n = 1564) with singleton pregnancies who attempted vaginal delivery and delivered infants weighing at least 4000 g, in two French tertiary care centers from 2005 to 2008, were included in our study. The studied outcome was maternal complications defined as composite item including the occurrence of a third- or fourth-degree perineal laceration, or the occurrence of severe postpartum hemorrhage requiring the use of prostaglandins, uterine artery embolization, internal iliac artery ligation or haemostatic hysterectomy, or the occurrence of blood transfusion. Univariate analysis, multivariable logistic regression and estimation of attributable risk were used. RESULTS: Maternal complications were increased in Asian women (adjusted odds ratio [aOR], 3.1; 95% confidence interval [CI], 1.1–9.3, Attributable risk (AR): 3%), in prolonged labor (aOR = 1.9 [95% CI; 1.1–3.4], AR = 12%) and in cesarean delivery during labor (aOR = 2.2 [95% CI; 1.3–3.9], AR = 17%). Delivering infants with a birthweight > 4500 g also increased the occurrence of maternal complications (aOR = 2.7 [95% CI; 1.4–5.1]) but with an attributable risk of only 10%. Multiparous women with a previous delivery of a macrosomic infant were at lower risk of maternal complications (aOR = 0.5 [95% CI; 0.2–0.9]). CONCLUSION: In women delivering infants with a birthweight of 4000 g or greater, some maternal characteristics as well as labor parameters may worsen maternal outcome beyond the influence of increased fetal weight.